Cognitive Simulation Using Mental Rehearsal for Procedural Learning in Medical Students: A Narrative Review - Khang Duy Ricky Le (Journal of Medical Education and Curricular Development)
Mental rehearsal, defined as the deliberate cognitive rehearsal of tasks without action, is an emerging approach to procedural skills learning in healthcare education. In particular, mental rehearsal has been associated with durable improvement of complex skills in various fields such as aviation, high performance sports and surgery. Despite this, mental rehearsal-based practices in healthcare are challenged with mainly informal and highly heterogeneous practice. Given this, the efficacy of mental rehearsal in medical education remains poorly characterised. Furthermore, there is currently no evidence-based approach to integrating mental rehearsal in the medical curriculum, nor frameworks to guide development of mental rehearsal skills for students. This narrative review explores mental rehearsal in medical education and evaluates the current principles of mental rehearsal and how these can be applied to improve procedural skills learning for medical students.